DOMESTIC VIOLENCE IN THE FAMILIES OF MILITARY SERVANTS - Litvinova, Iryna; Kulakevych, Anastasiia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: to investigate the normative foundations, causes and consequences of domestic violence among Ukrainian servicemen during the Russian-Ukrainian war. Research methods: documentary analysis and synthesis, analysis of objective data from law enforcement and military structures, etc. Research methods: the main causes of domestic violence among servicemen during the war are summarized, in particular psychological and social factors. Results: the main causes of domestic violence among military personnel during the war, including psychological and social factors, are summarized. The level of the regulatory framework for preventing and responding to such cases is determined and ways to improve the system of support for servicemen and their families are identified. Discussion: the effects of combat stress, PTSD, prolonged separation from family, and social isolation can lead to emotional distance, increased irritability, and communication difficulties within military families. These factors often contribute to misunderstandings, conflict, and in some cases, domestic violence. Addressing these challenges requires a comprehensive approach that includes legal measures, psychological rehabilitation, and family support programs. Establishing regular counseling sessions, support groups, and specialized training for soldiers and their families can help mitigate the negative effects, promote healthier relationships, and facilitate reintegration into civilian life. Building resilience within military families is essential to prevent long-term psychological and emotional strain. By fostering open communication and promoting awareness of mental health resources, families can better navigate the challenges associated with military life. Additionally, expanding access to crisis hotlines and emergency counseling services can provide immediate support during periods of heightened stress. Encouraging greater community involvement and social reintegration programs can also reduce the sense of isolation experienced by returning soldiers. Ultimately, a proactive and multi-faceted approach can strengthen family bonds, reduce the risk of domestic violence, and promote overall well-being for both service members and their loved ones.